Climate Adaptation in Construction Towards Zero Emission: Case Study in Vietnam - Thi Somg LE; Cao Chien LE; Jae Yoon SHIN; Tea Gyun YUN; Sung Uk JOO; Sang Moon LEE; Trung Thanh LE; Thi Tam NGUYEN (PT Keberlanjutan Strategis Indonesia, 2024)
Low energy consumption significantly contributes to new and retrofitting buildings when emphasizing energy efficiency. Although the mandatory requirements for U-factor and R-value are described in the Vietnamese National Technical Regulation on energy efficiency buildings - QCVN09:2017/BXD, these values have yet to be widely published, leading to designers' difficulties in choosing suitable materials at the design stage. The research involved a literature review, selection of criteria from global energy programs, developing a building materials labeling program in Vietnam, and a case study on insulation products to test its applicability. This paper focuses on the method ofdeclaring heat transfer values of building materials based on the energylabeling process. The study aims to build an energy labeling program for building materials. Criteria and labeling procedures for windows, doors, walls,and building roofs have been developed to accomplish these objectives. In addition, a case study for labeling insulation products was researched to evaluate the applicability of the developed labeling program in the implementation phase.